2013
DOI: 10.1016/j.ocemod.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parameterized lee wave drag on the energy budget of an eddying global ocean model

Abstract: The impact of parameterized topographic internal lee wave drag on the input and output terms in the total mechanical energy budget of a hybrid coordinate high-resolution global ocean general circulation model forced by winds and air-sea buoyancy fluxes is examined here. Wave drag, which parameterizes the generation of internal lee waves arising from geostrophic flow impinging upon rough topography, is included in the prognostic model, ensuring that abyssal currents and stratification in the model are affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 85 publications
2
76
0
Order By: Relevance
“…Using a hydrographic climatology and a similar parameterization for lee wave-driven mixing, Nikurashin and Ferrari (2013) and De Lavergne et al (2016) also show substantial water mass transformation in the Southern Ocean due to internal lee wave-driven mixing. Trossman et al (2013Trossman et al ( , 2016 implemented an inline wave drag parameterization (for both propagating and nonpropagating lee waves) from the atmospheric community (Garner 2005) into a high-resolution ocean general circulation model (Fig. 5d).…”
Section: Internal Lee Waves Theory and Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a hydrographic climatology and a similar parameterization for lee wave-driven mixing, Nikurashin and Ferrari (2013) and De Lavergne et al (2016) also show substantial water mass transformation in the Southern Ocean due to internal lee wave-driven mixing. Trossman et al (2013Trossman et al ( , 2016 implemented an inline wave drag parameterization (for both propagating and nonpropagating lee waves) from the atmospheric community (Garner 2005) into a high-resolution ocean general circulation model (Fig. 5d).…”
Section: Internal Lee Waves Theory and Observationsmentioning
confidence: 99%
“…Indeed, Wright et al (2014) found that the use of different stratification products yields a difference of up to 0.25 TW in the global conversion rate into lee waves. Conversion rates are even more sensitive to the near-bottom velocity field (Trossman et al 2013;Melet et al 2015), which can vary drastically with model resolution (Thoppil et al 2011) and should take into account mesoscale eddy velocities. Topographic blocking accounts for most of the predicted dissipation by the Garner (2005) scheme in the bottom 1000 m of two Southern Ocean domains (Trossman et al 2015).…”
Section: Internal Lee Waves Theory and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…How far from their generation site and how high in the water column lee waves dissipate their energy is largely unknown (e.g., Melet et al 2014). Over recent years, the potentially pivotal role of lee waves for the energy budget and dynamical balance of the Southern Ocean has been highlighted in several studies (e.g., Kunze et al 2006;Nikurashin and Ferrari 2010a;Trossman et al 2013;. Over recent years, the potentially pivotal role of lee waves for the energy budget and dynamical balance of the Southern Ocean has been highlighted in several studies (e.g., Kunze et al 2006;Nikurashin and Ferrari 2010a;Trossman et al 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, efforts have been focused on parameterizations of the generation and dissipation of internal tides (e.g., Jayne and St. Laurent 2001;Polzin 2009;Decloedt and Luther 2010;Melet et al 2013), which are the most energetic class of internal waves [with O(1) TW of energy being dissipated in the deep ocean]. As it has recently been shown that lee-wavedriven mixing has the potential to impact the ocean state in a climate model (Melet et al 2014), the energy budget of the ocean eddies, and the large-scale circulation (Trossman et al 2013), as well as the deep ocean turbulent mixing (Gille et al 2000;Ito and Marshall 2008;Saenko et al 2012;Nikurashin and Ferrari 2013), parameterizing lee-wave-driven mixing in climate models warrants serious consideration (MacKinnon 2013). As it has recently been shown that lee-wavedriven mixing has the potential to impact the ocean state in a climate model (Melet et al 2014), the energy budget of the ocean eddies, and the large-scale circulation (Trossman et al 2013), as well as the deep ocean turbulent mixing (Gille et al 2000;Ito and Marshall 2008;Saenko et al 2012;Nikurashin and Ferrari 2013), parameterizing lee-wave-driven mixing in climate models warrants serious consideration (MacKinnon 2013).…”
Section: Introductionmentioning
confidence: 99%